Impact of Ladder Drill and Pro-Agility Drill Training on Change of Direction Performance in Elite Amateur Futsal Athletes - Dwi Yudha Kurniawan; Sapta Kunta Purnama; Slamet Riyadi (Bulletin of Community Engagement, 2026)
COD ability is an important physical element in futsal, which requires numerous accelerations, decelerations, and energy transfers in short spaces. The impact of different training interventions on agility in different age groups is not currently known. The purpose of this study was to examine the effects of the ladder drill and pro agility drill on COD performance in elite amateur futsal athletes aged 17 years and under (U17) and over 19 years (U19), as well as determine the main effects for age compared with training method. A multistage sequence of changes of direction (COD) was implemented as part of a multi-week intervention in which 32 U17 and U19 athletes were tested for pre- and post-training performance. The results indicated that COD performance significantly increased in all groups after the two different training methods. The average increase in performance was greater in U19 than U17 athletes, which is a surprising finding since this suggests that there may be an effect of age on training response. The type of training also had minimum but significant differences between PAg, which showed a slightly greater effect, especially among U19s. Interaction analysis revealed age depended on the effectiveness of training. The ladder drill proved more effective for U17s and the pro agility drill for U19s. These findings indicate that there are variances in neuromuscular maturation, motor control, and biomechanical capabilities across age. Ladder drills and pro agility drills have been considered effective for training for the improvement of COD performance in young futsal players, but age may influence training response.